‘The art of happiness: a handbook for living’ and self-help books on happiness: a Foucauldian discourse analysis = ‘The art of happiness: a handbook for living’ và diễn ngôn về hạnh phúc: một nghiên cứu diễn ngôn theo Foucault - Nguyễn, Thúy Hạnh (2021)
This thesis is a humanities-oriented study that explores the historical conditions for the emergence of self-help discourse on happiness and how the book The Art of Happiness: A Handbook for Living manifests self-help discourse on happiness. Situated within a Foucauldian framework, it regards the account of self-help discourse’s historical conditions as an explanation for the intelligibility of self-help discourse. The American traditions including the puritan tradition, the individualism value and the tradition of adult self-education provide fertile soil for self-help discourse to flourish. The context of neoliberalism and globalization which entails the rise of positive psychology then fosters the popularity of self-help discourse on happiness. The other focus of the study is to investigate how The Art of Happiness: A Handbook for Living presents self-help discourse on happiness by looking into technologies of power and technologies of the self in the book. The research findings reveal that experts and psychology science are made use of to establish a set of normative rules, thereby exercising authority over individuals. Simultaneously, individuals govern themselves by adopting exercises of self-diagnosis, self-assessment and meditation. Technologies of the self in AOH are not in the shape of scientifically calculable but a range of meditation practices to train the mind. A different perspective of suffering is also presented in AOH.